Les ambiguïtés du paysage forestier des Landes de Gascogne - Aude Pottier (Projets de Paysage)
The forest of Landes de Gascogne which is an artificial landscape, cannot by no means be reduced to the mainstream vision of motorists crossing this area to reach their vacation places. Indeed, behind what might at first sight appears monotonous, a forest dedicated to production, one might actually consider a very diversified environment. On one hand, this last characteristic is often ignored by the public, while on the other hand, authorities gives a particular care to its protection. The coastal side of the forest stands as a brand image for the whole set. But no matter if one considers only the esthetically valued or well-known part of it, the forest of Landes de Gascogne cannot be dissociated anymore from consideration on natural values. This statement, applied to an artificial forest, is actually highly questioning.